La Gestión Presupuestaria en el Gobierno Autónomo Descentralizado parroquial rural de San Luis de Pambil, provincia de Bolívar en el año 2017 - Aldaz García, Diego Alexander (2018)
The Parochial Decentralized Autonomous Governments as of 2008 have assumed economic, financial and administrative autonomy that they did not previously have, these responsibilities have benefited them in many aspects, offering the possibility of planning based on the needs of their community, which It is very convenient as long as the authorities that manage these processes do it in a coherent and efficient way, but on the contrary the reality is different, the budgetary management can not be fulfilled in its entirety, in addition it must be mentioned that being a public institution it is subject to the supervision and control of state agencies that oversee the proper administration of the resources assigned by the central government, because of this the problem is born. What is the influence of the non-application of budgetary and financial indicators on the degree of efficiency in the execution of the budget execution uestaria in the Rural Parochial Decentralized Autonomous Government of San Luis de Pambil, Bolívar province in the fiscal year 2017 ?. Based on the above-mentioned problems, the following hypothesis is proposed: The application of budgetary and financial indicators will allow determining the degree of efficiency in compliance with budget execution in the Rural Parochial Autonomous Decentralized Government of San Luis de Pambil, Bolívar province in the period fiscal 2017 ?, to validate the hypothesis the survey and interview were used, in this sense very valuable information was obtained from the officials and the president of the Parish GAD of San Luis de Pambil detailed below: the community feels very dissatisfied with the current management, the budgetary cycle has not been fully met and finally it was detected that budgetary and financial indicators that measure the efficiency level of budget management are not applied, because of the above it was concluded that there is a need to apply a proposal that uses budgetary and financial indicators as a technical tool for evaluating budget management, which provides the opportunity to optimally execute the resources allocated and improve the image of the current administration before the community.